Oxidative Stress, Neuroinflammation and Mitochondria in the Pathophysiology of Amyotrophic Lateral Sclerosis - Elena Obrador; Rosario Salvador; Rafael López-Blanch; Ali Jihad-Jebbar; Soraya L. Vallés; José M. Estrela (MDPI AG, 2020)
Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron (MN) disease. Its primary cause remains elusive, although a combination of different causal factors cannot be ruled out. There is no cure, and prognosis is poor. Most patients with ALS die due to disease-related complications, such as respiratory failure, within three years of diagnosis. While the underlying mechanisms are unclear, different cell types (microglia, astrocytes, macrophages and T cell subsets) appear to play key roles in the pathophysiology of the disease. Neuroinflammation and oxidative stress pave the way leading to neurodegeneration and MN death. ALS-associated mitochondrial dysfunction occurs at different levels, and these organelles are involved in the mechanism of MN death. Molecular and cellular interactions are presented here as a sequential cascade of events. Based on our present knowledge, the discussion leads to the idea that feasible therapeutic strategies should focus in interfering with the pathophysiology of the disease at different steps.